Synthesis of Hierarchically Structured Metal−Organic Frameworks by a Dual‐Functional Surfactant. Issue 19 (22nd May 2018) - Duan, Chongxiong; Zhang, Hang; Peng, Anguo; Li, Feier; Xiao, Jing; Zou, JiFei; Luo, Shaojuan; Xi, Hongxia
Abstract: Hierarchically structured metal−organic frameworks (H−MOFs) are of great importance because of their widespread applicability in gas storage, separation, and catalysis. However, the synthesis of H−MOFs with tunable porosity and high stability is still a tremendous challenge. Herein, two strategies are developed to prepare classical porous MOFs—hierarchically structured HKUST−1 (H‐HKUST−1): (1) through utilizing a dual‐functional surfactant as a template individually, H‐HKUST−1 was successfully synthesized in a solvothermal system. The obtained H‐HKUST−1 products possess well‐ordered mesopores together with high thermal stability, the porosity of H‐HKUST−1 depends on the amount of the template and the type of extraction solvents. The multi‐ammonium head of the introduced surfactant bonded with BTC 3− anion to form the main framework while the long alkyl chain filled the space to form mesopores. (2) H‐HKUST−1 was also prepared rapidly at room temperature and ambient pressure through the simultaneous addition of a dual‐functional surfactant and zinc oxide (ZnO). The synthesis time was only 1 min, with a space–time yield (STY) for the as‐synthesized H‐HKUST−1 as high as 3.1 × 10 4 kg⋅m −3 ⋅d −1, which is at least one order of magnitude higher than previously reported results. The present approach opens up new avenues for the templated synthesis of stable H−MOFs with tunable porosity and high stability for a wide range of applications. Abstract : Two strategies are developed to prepare hierarchically structured HKUST−1: (1) a conventional solvothermal method, and (2) a room‐temperature rapid synthesis method. The obtained HKUST−1 products possess well‐ordered mesopores together with high thermal stability, the porosity of HKUST−1 depends on the amount of the template and the type of extraction solvents. Moreover, the space–time yield (STY) of as‐synthesized HKUST−1 was as high as 3.1 × 10 4 kg⋅m −3 ⋅d −1, which is at least one order of magnitude higher than previously reported results.